Algoritmo de gradientes conjugados aplicado à identificação de parâmetros nas equações de propagação de onda de cheia - Cirilo, José Almir (1979)
The development and application of optimization techniques to the parameters identification problem in flood propagation equations are presented. This work was basically developed by means of the following steps: a) presentation of Preissmann Implicit Method to the solution of unsteady open channel flow equations; b) study of factors affecting the equations parameters; c) presentation of gradient search optimization techniques; d) the association of Preissmann's scheme with gradient search techniques to develop parameters identification algoritms; e) application of the developed algoritm to the simulation of wave flood propagation in Capibaribe River with time-variable parameters.